2023
DOI: 10.3390/su152115326
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Small Ruminant Production in Low- and Middle-Income African Countries: Harnessing the Potential of Agroecology

Antoinette Simpah Anim-Jnr,
Prince Sasu,
Christine Bosch
et al.

Abstract: The role of small ruminant production in achieving sustainable and resilient food systems in low- and middle-income countries (LMICs) is yet to be fully explored or incorporated into current agroecological practices and policies. This review examines the principles and practices of agroecology, focusing on circular food systems and the sociopolitical aspects of their implementation for small ruminant production in LMICs. It discusses Gliessman’s five levels of agroecological transition and eight principles for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 153 publications
(159 reference statements)
0
1
0
Order By: Relevance
“…Small ruminants are adept at digesting lignocellulosic agro-industrial byproducts. Therefore, digestible food waste, such as fruit and vegetable byproducts, can also be utilized as a feed supplement for ruminants [ 78 , 79 ]. For example, when adult sheep were fed dietary combinations made from varying quantities of fruit waste, as conducted by Sahoo et al [ 51 ], it was found that, without changing feed intake, the supplemented groups had considerably improved CP and DM digestibility by 7.3 and 7.6% and 5.5 and 7.2%, respectively.…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%
“…Small ruminants are adept at digesting lignocellulosic agro-industrial byproducts. Therefore, digestible food waste, such as fruit and vegetable byproducts, can also be utilized as a feed supplement for ruminants [ 78 , 79 ]. For example, when adult sheep were fed dietary combinations made from varying quantities of fruit waste, as conducted by Sahoo et al [ 51 ], it was found that, without changing feed intake, the supplemented groups had considerably improved CP and DM digestibility by 7.3 and 7.6% and 5.5 and 7.2%, respectively.…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%